Association of reactive hyperglycemia, D-dimer, and asymmetric dimethylarginine (ADMA) with outcomes in acute ischemic stroke - Imran Imran; Syahrul Syahrul; Nasrul Musadir (Narra X, 2026)
Acute ischemic stroke is frequently accompanied by stress-related (reactive) hyperglycemia and may involve coagulation activation and endothelial dysfunction, reflected by D-dimer and asymmetric dimethylarginine (ADMA) levels, respectively. These factors may influence clinical outcomes. The aim of this study was to evaluate the associations of reactive hyperglycemia, D-dimer, and plasma ADMA with stroke outcomes in patients with acute ischemic stroke. A cross-sectional study was conducted among patients with acute ischemic stroke admitted to the neurology ward and stroke unit of Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia, between May and September 2024. Functional stroke outcome (FSO) was assessed using the Barthel Index, and disability stroke outcome (DSO) was assessed using the modified Rankin Scale (mRS). A total of 123 patients were included. The findings indicate that mean admission blood glucose was significantly higher in the improved FSO group than in the unchanged-worsened group (p=0.004), whereas mean blood glucose did not differ significantly across DSO categories (p=0.194). Mean D-dimer was significantly higher in the unchanged-worsened FSO group than in the improved group (538.6±249.4 vs 398.4±128.5 ng/mL; p<0.001). Across DSO categories, D-dimer showed a significant difference only between the no-disability and moderate-disability groups (p=0.044), without a consistent graded pattern. Mean ADMA levels were not significantly different between FSO groups (p=0.136), but it was statistically significant between DSO categories (slight vs moderate disability), p=0.045. The present analysis indicated that elevated D-dimer, dyslipidemia, heart disease, and GCS were significantly associated with FSO. Systolic blood pressure, diastolic blood pressure, reactive hyperglycemia, and hypertension were significantly associated with DSO severity. Overall, elevated D-dimer was more strongly associated with Barthel Index-based functional outcome, whereas reactive hyperglycemia was associated with mRS-based disability outcome.